Effect of sivelestat sodium on the incidence of ventilator-associated pneumonia in patients with sepsis and ARDS - Zhang, Xingcheng; Li, Zhuangli; Lei, Xiqun; Wang, Huaxue; Shan, Nanbing; Sun, Yun (Frontiers in Medicine, 2025)
ObjectivesTo evaluate the efficacy of sivelestat sodium in reducing ventilator-associated pneumonia (VAP) in patients with sepsis and acute respiratory distress syndrome (ARDS).MethodsA retrospective analysis was performed on the clinical data of 187 adult patients with sepsis combined with ARDS admitted to the intensive care unit (ICU) of Fuyang Second People’s Hospital from 1 January 2022 to 1 December 2024. Among these patients, 60 received sivelestat sodium as part of their treatment, while 127 did not. The treatment efficacy indices were oxygenation index (PaO2/FiO2), procalcitonin (PCT), C-reactive protein (CRP), and interleukin-6 (IL-6) levels (all measured before and within 7 days of treatment), and VAP, bacteremia, time to first mechanical ventilation, CRRT, length of stay in ICU, length of stay, and 28 days mortality.ResultsThere were no significant differences in age, sex, comorbidities, use of hormones, use of vasoactive drugs, APACHE II score, or SOFA score between the two groups before treatment. Compared with patients who did not receive sivelestat sodium, those treated with sivelestat sodium had significantly lower incidences of VAP (χ2 = 6.910, P = 0.009) and bacteremia (χ2 = 5.372, P = 0.023), as well as shorter times to first mechanical ventilation (t = −2.071, P = 0.041) and ICU stays (t = −2.085, P = 0.039). At 28 days, the fatality rate in the sivelestat group was 33.33%, and that in the control group was 34.65%, although this slight reduction was not significant (χ2 = 0.031, P = 1.000). There was also no significant difference in the length of stay between the two groups (t = −0.609, P = 0.054). Log-Rank test analysis revealed that the time without VAP in the sivelestat group was significantly longer than that in the control group (χ2 = 7.600, P = 0.006). After adjusting for APACHE II score and age, COX proportional risk model analysis revealed that the 28 days survival risk for VAP with sivelestat sodium was 34.67% higher than that in the control group (Z = −2.537, P = 0.011).ConclusionSivelestat sodium therapy was associated with a reduced incidence of VAP and a shorter ICU stay in patients with ARDS. However, there was no significant benefit on 28 days survival or total hospital stay.